1998
DOI: 10.1002/(sici)1097-4601(1998)30:1<7::aid-kin2>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of L-glutamine by manganese(iii) in aqueous sulfuric acid, acetic acid, and pyrophosphate media: A kinetic and mechanistic study

Abstract: Manganese(III) solutions were prepared by known electrochemical methods in sulfuric acid, acetic acid, and pyrophosphate media. The nature of the oxidizing species present in manganese(III) solutions was characterized by spectrophotometric and redox potential measurements. Kinetics of oxidation of L-glutamine by manganese(III) in sulfuric acid (1.5 M), acetic acid

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 11 publications
2
6
0
Order By: Relevance
“…Thus, we conclude that the new spectra (Figures 4 and 5) are that of the manganese(III)-EDTA complex with l max ¼ 500 nm. Our l max values are in good agreement with the literature values [22]. On the other hand, stable Mn(III)-EDTA complex is not formed in the absence of externally added Mn(II) (vide supra, Table 2).…”
Section: Preparation and Characterisation Of Colloidal Mno 2 By The Osupporting
confidence: 91%
“…Thus, we conclude that the new spectra (Figures 4 and 5) are that of the manganese(III)-EDTA complex with l max ¼ 500 nm. Our l max values are in good agreement with the literature values [22]. On the other hand, stable Mn(III)-EDTA complex is not formed in the absence of externally added Mn(II) (vide supra, Table 2).…”
Section: Preparation and Characterisation Of Colloidal Mno 2 By The Osupporting
confidence: 91%
“…Some studies have been reported on the kinetics of Mn III oxidations of various substrates like formaldehyde [7], dipeptides [8] and amino acids [9] in perchloric, sulfuric, acetic, and pyrophosphate medium [10,11]. Extensive work has been reported on the kinetics of oxidation of amino acids like glycine [12], methionine [13], threonine [14], and other amino acids [15] by Mn III as oxidant.…”
Section: Introductionmentioning
confidence: 99%
“…Sulfuric acid applied in these experiments is expected to affect the oxidation kinetics via complexation of the oxidant and protonation of the reductant. To the best of our knowledge, data on oxidation processes by manganese(III) in sulfuric acid media are so far limited to a study of the kinetics of L-glutamine oxidation by Made Gowda et al [19].…”
Section: Introductionmentioning
confidence: 99%